The Influence of Social Capital and Social Role on Starting Wage for People With and Without Disabilities. (October 2018) - Phillips, Brian N.; Strauser, David R.; Ritter, Ellen S.; Notaro, Stephen J.; Jones, Weneaka D.
People with disabilities are arguably the most economically marginalized population in America. Employment does not address the problem unless wages reach adequate levels, suggesting the need for better understanding of factors influencing compensation in employment. The purpose of this study is to replicate previous findings on social capital and starting wage while also considering the influence of social role for people with and without disabilities. The responses of university health students to hypothetical hiring scenarios were analyzed using a three-way mixed ANOVA. Results support and extend prior research suggesting that social capital and social role have a positive influence on starting wage for both people with and without disabilities. Scenarios depicting social capital and positive social role resulted in an increase in hourly wage of more than US1, 500.00 per year than those with low levels of social capital and a negative social role. A similar but weaker relationship between pay and social capital existed when there was one degree of separation (i.e., the friend of a friend) between employer and new employee. Social role, along with social capital, is an important factor in starting wage decisions. Implications for the job search are provided.